IRAN’S STRATEGIC NARRATIVE AND DEFENSIVE POSTURE IN THE U.S.–ISRAEL CONFLICT: PERCEPTIONS, JUSTIFICATIONS, AND REGIONAL IMPLICATIONS - WOSU, Moses Victor; UROM, Charles Egwu (PT. Antis International Publisher, 2026)
Objective: This paper explored the Iranian strategic discourse and defensive stance in relation to the U.S.Israel war, and how perceptions, reasons and implications in the region influenced its actions. Method: Based on the Realist theory and the principle of a security dilemma, the study examined the hybrid military approach of Iran, integrating defensive, asymmetric, and proxy warfare to maintain sovereignty and prevent foreign aggression. The study employed a qualitative approach that relies on secondary sources; such as academic literature, policy statements, and regional accounts on the interplay between the ideological narrative of defense, legitimacy, and resistance of Iran and its behavioral patterns. Results: The research showed that there is a considerable gap in perceptions: in the United States and Israel, the same actions were interpreted as signs of expansionist intentions and destabilizing actions, which would strengthen the security dilemma, whereas Iran saw the same actions as defensive ones and the need to preserve the regime. The discussion has indicated that the strategic narrative of Iran has been the key to justification of its policy in the domestic context and persuasion of the international audience, but it has not been effective in all cases and circumstances. The paper came to the conclusion that the strategic discourse and defensive stance of Iran could not be separated, and ideology, perception, and operational behavior were all integrated in the Iranian security policy. Its compromise nature helped Iran to survive in a hostile region without being deterred, but at the same time, created more tension with its opponents because of conflicting interpretations. On the basis of these results, the study suggested creating a multilateral dialogue platform to clarify the intentions and enhance the communication process, creating defensive strategies to combat hybrid threats and asymmetric operations, and enhancing the strategic narrative through transparency, public diplomacy, and information campaigns based on research. Such steps would help to increase mutual understanding, decrease the number of misperceptions, and help to create a more stable regional security environment. Novelty: Based on the Realist theory and the principle of a security dilemma, the study examined the hybrid military approach of Iran, integrating defensive, asymmetric, and proxy warfare to maintain sovereignty and prevent foreign aggression.